THE ACTS OF RACIAL DISCRIMINATION TO THE BLACKS AS SEEN IN STOCKETT S THE HELP - Nanlohy, Olivia; Rorintulus, Olga; Kamagi, Sarah (English Education Department, 2021)
This study aims to determine the actions of racial discrimination committed by white people against black people in The Help < em>This research used qualitative method in terms of using words or text In conducting this research the data are collected from primary and secondary sources The primary source is the novel entitled The Help< em> written by Kathryn Stockett The second sources are some related books and articles from the internet that are supporting this research The result of this study is presented descriptively As the result of this research the researcher found that there are many actions of racial discrimination reflected in The Help< em> It can be seen in some several sections First there is a Discriminatory Law namely Jim Crow Law of the Southern United States Second the Discriminatory Stereotypes that the white people created about the black people such as Blacks are dirty Black people are Thieves Black People as Diseases and Black People are Dumb And the last is the Discrimination in Public Services that can be found in residential area library education health services voting and public transportation < p>